Video tutorial-based multimedia development for the Bridal Makeup subject at SMK Pemda Lubuk Pakam - Elyda Mariam Manurung; Harun Sitompul; R. Mursid (Universitas Pendidikan Indonesia, 2025)
The dearth of understanding and the paucity of accessible learning materials concerning the concept of Batak Toba bridal makeup have resulted in substandard achievement of the minimum completion criteria and challenges in practical work in bridal makeup lessons. In response to these issues, the objective of this study is to develop a multimedia-based video tutorial for the Batak Toba bridal makeup subject at SMK Pemda Lubuk Pakam. The tutorial is designed to serve as a practical, engaging, and effective learning tool. The research method employed is the Borg and Gall research and development method, consisting of eight stages: needs analysis, validation, student testing, and final product development. The research subjects consisted of 30 students, who were divided into an experimental group and a control group. Experts in design, content, and media conducted the validation of product development. The study's results indicate that the developed media are suitable for use and are considered practical and effective in supporting the learning process. The Batak Toba bridal makeup video tutorial will likely serve as an alternative learning medium for bridal makeup, thereby enhancing students' skills in this area. Abstrak Keterbatasan pemahaman serta minimnya media pembelajaran yang dapat diakses oleh siswa terkait konsep tata rias pengantin Batak Toba berdampak kepada rendahnya ketercapaian kriteria ketuntasan minimal dan kesulitan praktikum pada mata pelajaran make-up pengantin. Berkaitan dengan permasalahan tersebut, penelitian ini bertujuan untuk mengembangkan multimedia berbasis video tutorial untuk mata pelajaran tata rias pengantin Batak Toba di SMK Pemda Lubuk Pakam sebagai media yang praktis, menarik, dan efektif. Metode yang digunakan dalam penelitian ini adalah metode penelitian dan pengembangan Borg and Gall dengan delapan tahapan, mulai dari analisis kebutuhan, validasi, uji coba siswa hingga produk akhir. Subjek penelitian melibatkan 30 siswa yang dibagi dalam kelas eksperimen dan kelas kontrol. Validasi pengembangan produk dilakukan kepada ahli desain, materi dan media. Hasil penelitian menunjukan bahwa media yang dikembangkan sudah layak untuk digunakan dan dinilai praktis serta efektif dalam mendukung proses pembelajaran. Berdasarkan hal tersebut, diharapkan dengan adanya video tutorial make up pengantin Batak Toba yang dihasilkan ini dapat menjadi alternatif media pembelajaran make-up penganti yang mampu untuk meningkatkan keterampilan tata rias pengantin siswa. Kata Kunci: Borg and Gall; mata pelajaran tatarias pengantin; multimedia; video tutorial